From 'Pretty' to 'Pretty Powerful': The communicatively constituted power of facial beauty's performativity. Issue 12 (December 2021) - Hollis, David; Wright, Alex; Smolović Jones, Owain; Smolović Jones, Sanela
The face is a significant locus of power upon which judgements concerning a person's status, worth and attractiveness are made. This study contributes to knowledge of facial norms' shifting performative power in daily organizing, theorizing facial beauty as a communicatively constituted authoritative text. We achieve this through blending Butlerian and communication as constitutive of organization (CCO) theorizing. This allows us to enrich understandings of power and performativity's necessarily entangled and co-constitutive unfolding, as we trace how a normative understanding of facial beauty becomes more and/or less performatively powerful through embodied-textual processes. Our theorizing is generated from an ethnography of a UK cosmetics firm and demonstrates how facial beauty functions as a (figurative) authoritative text that corporealizes, subjectivizes and is resisted by makeup artists within a confluence of (concrete) text and conversation. We show how through communicative, citational and embodied processes of corporealization, regulation and subjection, everyday performances like makeup applications become performatively powerful on the ground level of interaction. Further, returning authoritative texts to their original figurative formulation uncovers something of how their transformative power shapes organizing's ongoing accomplishment.